Chopin: Visual Contexts - Szerszenowicz, Jacek (Interdisciplinary Studies in Musicology, 2018)
The drawings, portraits and effigies of Chopin that were produced during his lifetime later became the basis for artists’ fantasies on the subject of his work. Just after the composer’s death, Teofil Kwiatkowski began to paint Bal w Hotel Lambert w Paryżu [Ball at the Hotel Lambert in Paris], symbolising the unfulfilled hopes of the Polish Great Emigration that Chopin would join the mission to raise the spirit of the nation. Henryk Siemiradzki recalled the young musician’s visit to the Radziwiłł Palace in Poznań. The composer’s likeness appeared in symbolic representations of a psychological, ethnological and historical character. Traditional roots are referred to in the paintings of Feliks Wygrzywalski, Mazurek - grający Chopin [Mazurka - Chopin at the piano], with a couple of dancers in folk costume, and Stanisław Zawadzki, depicting the composer with a roll of paper in his hand against the background of a forest, into the wall of which silhouettes of country children are merged, personifying folk music. Pictorial tales about music were also popularised by postcards. On one anonymous postcard, a ghost hovers over the playing musician, and the title Marsz żałobny Szopena [Chopin’s funeral march] suggests the connection with real apparitions that the composer occasional had when performing that work. In the visualisation of music, artists were often assisted by poets, who suggested associations and symbols. Correlations of content and style can be discerned, for example, between Władysław Podkowinski’s painting Marsz żałobny Szopena and Kornel Ujejski’s earlier poem Marsz pogrzebowy [Funeral march]. The testimony of people who visited the Cracow apartment of Stanisław Przybyszewski suggests crucial links between Wojciech Weiss’s lost painting Chopin that hung there and the host’s aesthetic writings and legendary sessions of nocturnal improvisations. Against the background of that iconography, Jerzy Duda-Gracz’s idea of painting all Chopin’s works, subsequently brought together in the cycle Chopinowi Duda-Gracz [From Duda-Gracz for Chopin], is quite exceptional, in terms of its genesis, the extent of Chopin’s oeuvre and also the way in which music is transformed into painting. The artist attempted to capture the atmosphere of Polish landscapes visited by the composer, linking them to particular works. The Chopin cycle possesses a clear stylistic and symbolic identity, although it is impossible to establish a universal pattern for translating music into visual art. Although Zbigniew Rybczyński employed a camera and advanced cinematographic techniques, his depiction of Chopin’s Marche funebre from the Sonata in B flat minor (in his suite of films The Orchestra) refers to Romantic-symbolic interpretations and to previous pictorial visualisations. The director dresses his actors in historical costumes and places them in front of the Paris Opera. To the rhythm of Chopin’s music, they play out - using theatrical expression typical of silent film, pantomime, ballet and tableaux vivants - a story of maturing and ageing.